2007
DOI: 10.1210/jc.2006-2668
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels and Adipose Tissue Messenger Ribonucleic Acid Expression of Retinol-Binding Protein 4 Are Reduced during Calorie Restriction in Obese Subjects but Are Not Related to Diet-Induced Changes in Insulin Sensitivity

Abstract: Context: Retinol-binding protein 4 (RBP4) may play a role in the development of insulin resistance. Objective:We investigated whether RBP4 adipose tissue mRNA expression and plasma level are related to insulin sensitivity during a diet-induced weight loss.Design, Setting, Patients, and Intervention: Obese women followed a dietary intervention composed of a 4-wk very low-calorie diet (VLCD), a 2-month low-calorie diet, and 3-4 months of a weight maintenance (WM) phase. Main Outcome Measures:Clinical investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 23 publications
12
81
3
1
Order By: Relevance
“…Indeed, the RBP4 treatment of human adipocytes increased, rather than decreased, the amount of glucose transporter (GLUT)4 at the plasma membrane and thereby increased basal glucose uptake (18). This is further supported by reports demonstrating a positive relationship between adipose tissue RBP4 and GLUT4 mRNA levels in adipose tissue from obese subjects (19). Thus, an increased circulating RBP4 would potentially increase glucose disposal, although we were unable to demonstrate an association with the temporal courses of glucose or insulin in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, the RBP4 treatment of human adipocytes increased, rather than decreased, the amount of glucose transporter (GLUT)4 at the plasma membrane and thereby increased basal glucose uptake (18). This is further supported by reports demonstrating a positive relationship between adipose tissue RBP4 and GLUT4 mRNA levels in adipose tissue from obese subjects (19). Thus, an increased circulating RBP4 would potentially increase glucose disposal, although we were unable to demonstrate an association with the temporal courses of glucose or insulin in our study.…”
Section: Discussionsupporting
confidence: 88%
“…We did not demonstrate a correlation between serum RBP4 levels and markers of insulin resistance in overweight women with PCOS at baseline, confirming previous observational PCOS studies (7,15). Other than that of Graham et al (4), most studies in weight-matched diabetic and obese subjects have not demonstrated a relationship with RBP4 and insulin resistance (5,6,8,10). We showed a correlation with RBP4 and triglycerides, which has been noted previously (4,15).…”
Section: Correlations With Change In Rbp4supporting
confidence: 89%
“…Relationships of RBP4 with features of the metabolic syndrome have also been inconsistently demonstrated (4,6,8). RBP4 has been shown to change with interventions that reduce insulin resistance, including weight loss (5,10), exercise (4), and insulin sensitizers, although results are variable (8,9). Methodological issues in the measurement of RBP4 may contribute to inconsistencies, with few studies using the recommended Western blot technique (11).…”
mentioning
confidence: 99%
“…Several studies found no correlation between circulating RBP4 levels, the level of obesity, and the amount and distribution of adipose tissue (9-11, 35, 72). In addition, several studies found no correlation between RBP4 adipose tissue mRNA expression and serum levels (9,10,44,73).…”
Section: Rbp4 In Childhood/adolescent Obesity and Insulin Resistancementioning
confidence: 99%
“…Significant decrease in weight, achieved by diet, exercise, or bariatric surgery, leads to a decrease in circulating and/or adipose tissue RBP4 levels (9,32,(42)(43)(44). The changes in RBP4 levels in non-diabetic subjects during weight loss were significantly correlated with the amount of visceral fat loss but were not associated with the amount of total body fat loss or abdominal subcutaneous fat loss (43).…”
Section: Characteristics Of Rbp4mentioning
confidence: 99%